Modification of Ceramics and Ceramic Glazers with Carbon Nanoadditives, and Properties of the Modified Materials - Zelenskii, Oleg; Shmalko, Volodymyr; Panov, Evgen; Shylovych, Tetiana; Shylovych, Yaroslav; Rudkevich, Maryan (Видавництво Львівської політехніки, 2019)
Розглянуто спосіб модифікації керамічних матеріалів внаслідок введення карбонових нанододатків у вигляді водної суспензії до складу шлікера і керамічної глазурі для виготовлення санітарно-технічної кераміки. Досліджено фізико-механічні властивості зразків. Отримано результати експериментальних досліджень властивостей композиційних матеріалів, наномодифікованих карбоновими наноструктурами.

The work describes a method of modifying the ceramic materials by introducing carbon-based nanoscopic additives into the slip composite and glaze composite in the form of water-based suspension for the production of sanitary and technical ceramics of increased quality. Physical and mechanical properties of experimental samples are researched. The results of experimental research are obtained in the form of experimentally determined properties of composite materials which were nanomodified by carbon nanostructures.
Модифікація карбоновими нанододатками кераміки і керамічної глазурі та властивості модифікованих матеріалів
Keywords: наноструктура; кераміка; глазур; санітарно-технічні вироби; пористість; крайовий кут змочування; nanostructure; ceramics; glazer; sanitary ware; porosity; contact angle of wetting